Reshaping beach morphology by modifying offshore breakwaters. (15th March 2018) - Pranzini, Enzo; Rossi, Lorenzo; Lami, Gabriele; Jackson, Nancy L.; Nordstrom, Karl F.
Abstract: Use of static shore protection structures is often considered an irreversible change toward a decrease in shoreline dynamism, but structures can be modified to make them more compatible with human needs and create a more mobile beach. This concept is documented by comparing changes in shape and volume of the beach and nearshore resulting from modification of emerged, segmented offshore breakwaters to a continuous submerged structure. Emerged, segmented breakwaters were constructed between 1983 and 1987 in Follonica Bay on the Tuscan coast of Italy. The breakwaters created an asymmetric shoreline with beach salients landward of the structures and bays landward of the gaps. Between 2011 and 2013, the breakwaters were removed and the boulders were used to create a continuous submerged breakwater farther offshore, with a wider crest at −0.5 m below mean sea level. The purpose was to achieve better views of the sea and a more equitable beach width alongshore. In the process, natural processes were allowed greater freedom to reshape the beach. The shoreline straightened after alteration, but retreated an average of 12.9 m between 2013 and 2016. This study provides one of the few prototype before-after evaluations of modifying breakwaters to make shorelines function more naturally. The results indicate how human-induced geomorphic changes can occur at the local scale (tens to hundreds of meters alongshore) in response to the perceived needs of local managers, even where the new condition runs counter to the traditional goal of creating a more stable beach for shore protection. Highlights: Protection structures can be modified to adapt to the economic landscape. Emerged, segmented breakwaters were reconfigured to a continuous submerged structure. An asymmetric shoreline of salients and bays became more dynamic and linear. The subaerial beach accreted initially, but then erosion occurred. Structures need not cause an irreversible change toward decreasing dynamism.